A brief but invaluable interview with Henry G. Widdowson (Polifonia, 1997)
ABSTRACT: Professor Widdowson has been teaching for many years at the University of London in Institute of Education. He has written many articles and several books on second language teaching and education, including Teaching Language as Communication (OUP, 1978), translated recently in Brazil by José Carlos P. de Almeida Filho as O Ensino de Línguas para a Comunicação (Pontes, 1993), and, more recently, Aspects of Language Teaching (OUP, 1990) and Linguistics (OUP, 1996). In 1995, a book called In Honor of H. G. Widdowsonwas written in his honour by some of his colleagues. He has been to Brazil several times for lectures and courses and is one of the most influential thinkers in the area of second/foreign language teaching for many Brazilians.